Preventing the Tyranny of the Majority - Experimental Evidence on the Choice of Voting Thresholds in Bayesian Games - Dirk Engelmann; Hans Peter Grüner; Timo Hoffmann; Alex Possajennikov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In democracies, an absolute majority of the population may choose policies that are harmful to the rest of the population. A purpose of super-majority rules is to prevent this from happening. We study whether individuals optimally choose sub- or super-majority rules when the rights of minorities should be protected. Subjects propose more extreme voting rules for more skewed distributions, but we also find that rule choices are biased towards balanced rules, leading substantial welfare losses.
Keywords: C91; 330